2014
DOI: 10.3897/zookeys.441.7646
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of the fungus gnats of Finland: Bolitophilidae, Diadocidiidae, Ditomyiidae, Keroplatidae and Mycetophilidae (Diptera)

Abstract: A checklist of the ’fungus gnat’ group of families in Sciaroidea: Bolitophilidae, Diadocidiidae, Ditomyiidae, Keroplatidae and Mycetophilidae (Diptera) recorded from Finland. At present, the known Finnish fauna comprises 767 recognized species in 78 genera; 21 species of the family Bolitophilidae, 5 of the family Diadocidiidae, 2 of the family Ditomyiidae, 47 of the family Keroplatidae and 692 of the family Mycetophilidae. The unassigned genus Sciarosoma Chandler, 2002 is not included in this paper because it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The species is widely distributed in Europe extending also to the Eastern Palearctic (Laštovka 1972, Chandler 2013, Jakovlev 2014). The material from Estonia represents a new country record.…”
Section: The Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The species is widely distributed in Europe extending also to the Eastern Palearctic (Laštovka 1972, Chandler 2013, Jakovlev 2014). The material from Estonia represents a new country record.…”
Section: The Speciesmentioning
confidence: 99%
“…Our records reveal saprotrophic members of the Agaricales as the host of this species. The species is widely distributed in Europe (Chandler 2013, Jakovlev 2014, Kjærandsen 2012) extending also to the Middle East and Eastern Palaearctic (Chandler 2013). The material from Georgia represents a new country record.…”
Section: The Speciesmentioning
confidence: 99%
“…This rare and poorly known European species was described from Great Britain (Edwards 1941, as Rhymosia) and was later recorded only from Poland (Zatwarnicki 2001, as Allodiopsis), Germany (Ševčík 2001), Finland (Jakovlev 2014), Sweden (Kjaerandsen et al 2007), Russian Karelia, Ukraine and Siberia (Zaitzev 2003); it is here reported for the first time from Romania. Immature stages are unknown, but most likely it is a forest associated species.…”
Section: Synplasta Gracilismentioning
confidence: 95%
“…The species has a wide range, extending from Great Britain (Chandler 2000) and Portugal (Ribeiro 2003) to the Russian Far East (Zaitzev 2003). In Europe the species is also known from France (Chandler 2013), Finland (Jakovlev 2014), and Russian Karelia (Zaitzev 2003). This species is very close to M. gratiosa Winnertz, and some of the records published as M. gratiosa may actually belong to M. deflexa (e.g., Polevoi 2001) from eastern Finland).…”
Section: Synplasta Gracilismentioning
confidence: 99%
See 1 more Smart Citation